Population of Rhizobium bacteria in the soil at several plant from Buton island, Muna regency, Southeast Sulawesi - Sri Purwaningsih (JOURNAL OF TROPICAL SOILS, 2009)
The research was conducted in order to know population of Rhizobium bacteria in the soil at several plant from Buton island, Muna regency, Southeast Sulawesi. The purpose of the study was to get the population data and pure cultures of Rhizobium bacteria.Rhizobium bacteria were isolated from 13 sample from rhizosphere of fruit plant, 14 sample soil from rhizosphere of yield plant, 5 sample soil from rhizosphere of horticulture plant, and 8 sample soil from forest plant. Isolation was done in standard medium Yeast Extract Mannitol Agar (YEMA), the inculation at (27-280C), and the population with plate count methods. The growth characteristic of strain was observed by using YEMA medium mixed respectively with Brom Thymol Blue and Congo Red as indicators.The population of Rhizobium bacteria was in the range of 7-115 X 105 CFU/g soil, and the highest population was found from the sample soil from rhizosphere with Ipomea batatas plant. Fourty nine gave of pure culture, thirty five isolates can be grouped as fast growing, while fourteen can be grouped as slow growing.